Web-based and mailed questionnaires: a comparison of response rates and compliance - Bälter, Katarina Augustsson; Bälter, Olle; Fondell, Elinor; Lagerros, Ylva Trolle (Epidemiology (Cambridge, Mass.), 2005)
We assessed response rates and compliance for a printed questionnaire and a Web questionnaire in a Swedish population-based study and explored the influence of adding personalized feedback to the Web questionnaire. We assigned 875 subjects to 1 of 3 groups: printed questionnaire, plain Web questionnaire, or Web questionnaire with personalized feedback. The questionnaire had 2 parts, first a general section and then a dietary section. The response rate for the general section was 64% for the printed questionnaire, compared with 50% for the Web questionnaire with feedback. For the dietary questionnaire, the rates were reversed, resulting in a total response rate for the dietary questionnaire that did not differ between printed and web questionnaire with feedback. Interactivity in the Web questionnaire increased compliance in completion of the second section of the questionnaire. Web questionnaires can be useful for research purposes in settings in which Internet access is high.